A KNIFE INJURY IN THE MAXILLOFACIAL REGION–A CASE REPORT - B.Blagova; S.Mitov; D.Krastev (Trakia Journal of Sciences)
Background:Head injuries are not so uncommon in emergency medicine. Generally, separate areas of the face and skull are affected. Some situations are challenging, especially when the traumatic foreign bodies are still inside tissues. So, every single clinical case should be thoroughly described to serve as a basis for an operative method and protocol creation for a therapeutic approach in future injuries of this type. In the current communication, we intend to report our experience with an incidentof a stab injury inmaxillofacial surgery.Methods: Amiddle-aged male patient with a stab wound in the face underwent surgical removal of the knife under intubation anesthesia in emergency conditions.Results:The postoperative period was uneventful. The patient was discharged on the fifth day with satisfactory early postoperative results.Conclusions:Together with the anatomical specifics of the region, the surgery for knife removal is more complicated and riskier than usual. On the other hand, exactly rich blood supply determines quick and uneventful wound healing.